Productivity and Economics of some Commercially Important Forest Trees - Srivastav, A. K. (Indian Forester, 1994)
Acacia nilotica, Dalbergia sissoo and Casuarina equisetifolia, these fast growing species have been planted under irrigated conditions in energy plantations and afforestation schemes in Gujarat State. Biomass production and cost benefit have been described in this paper.